Pharmacokinetics of Rolapitant in Patients With Mild to Moderate Hepatic Impairment. (12th January 2018) - Wang, Jing; Wang, Xiaodong; Zhang, Zhi‐Yi; Arora, Sujata; Lu, Sharon; Kansra, Vikram
Abstract: Rolapitant is a selective and long‐acting neurokinin‐1 receptor antagonist approved in an oral formulation in combination with other antiemetic agents for the prevention of delayed chemotherapy‐induced nausea and vomiting in adults. This was a phase 1 open‐label, parallel‐group pharmacokinetic and safety study of a single oral dose of 180 mg of rolapitant and its major active metabolite, M19, in subjects with mild and moderate hepatic impairment compared with healthy matched controls. Pharmacokinetics were assessed by a mixed‐model analysis of variance of log‐transformed values for maximum observed plasma concentration (Cmax ), observed time at Cmax (tmax ), area under the plasma concentration–time curve (AUC) from time 0 to the time of the last quantifiable concentration (AUC0–t ), and AUC from time 0 to 120 hours (AUC0–120 ), with hepatic group as a fixed effect. Mean rolapitant Cmax, AUC0–t, and AUC0–120 were similar in the mild hepatic impairment and healthy control groups. In subjects with moderate hepatic impairment, AUC0–t was similar and Cmax was 25% lower than in healthy controls. Mean M19 Cmax and AUC0–t were similar in the mild hepatic impairment group and healthy controls, but <20% lower in those with moderate hepatic impairment versus healthy controls. Fraction of unbound rolapitant was comparable in all groups for rolapitant and M19. Rolapitant was well tolerated in all groups, without serious adverse events. Pharmacokinetic differences between healthy subjects and those with mild or moderate hepatic impairment are unlikely to pose a safety risk and do not warrant predefined dosage adjustment in the presence of hepatic impairment.